Impact of Velocity and Wind Direction to Drag Force of Commercial Train Locomotive - Ahmad Imam Khoiruddin (Jurnal Teknik Mesin dan Mekatronika (Journal of Mechanical Engineering and Mechatronics), 2022)
An analysis of the relationship between locomotive speed and wind direction was carried out on the amount of drag force faced by the CC203 locomotive, one of the fastest locomotives used in Indonesia today. Based on the results of the analysis, an alternative geometry option was made for the CC203 locomotive’s nose. In the geometry option, changes are made to the front structure of the locomotive in order to reduce the amount of air drag that occurs. Based on the results of the analysis that has been carried out, the greater the speed of the locomotive, the value of the drag coefficient will tends to be constant, but the overall value of the drag force will increase. In addition, changes in wind direction facing the locomotive will also significantly increase the coefficient and air drag force. In changing the locomotive geometry, the results of geometric options are obtained that can significantly reduce the coefficient and total air resistance force. Locomotive velocity was assumed as resultant of wind velocity.